2011
DOI: 10.1111/j.1365-2435.2011.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clear and cloudy sky conditions on the vertical distribution of photosynthetic CO2 uptake within a spruce canopy

Abstract: Summary1. Cloud cover affects carbon exchange between biota and the atmosphere. Recent studies have demonstrated that an increase in the diffuse radiation fraction enhances the photosynthetic efficiency of canopies. Although the exact mechanism behind this effect is not clear, a more even distribution of light among leaves across the vertical profile of the canopy is considered to be the most important cause of this difference. 2. To test this hypothesis, the net ecosystem production (NEP) of a Norway spruce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
140
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 38 publications
(94 reference statements)
7
140
1
2
Order By: Relevance
“…Furthermore, we demonstrated that sun-grown sunflower leaves excessively absorb diffuse light in the upper palisade cells at the expense of light availability in the lower palisade and spongy mesophyll. Thus, the leaf-level photosynthetic response to diffuse light in sunflower occurred opposite to the expected canopylevel increases in LUE (Gu et al, 2002;Alton et al, 2007;Urban et al, 2007Urban et al, , 2012Alton, 2008;Kanniah et al, 2013;Williams et al, 2014;Cheng et al, 2015). We combined our leaf-level model with canopy-level observations of diffuse and direct light penetration to investigate this tradeoff (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we demonstrated that sun-grown sunflower leaves excessively absorb diffuse light in the upper palisade cells at the expense of light availability in the lower palisade and spongy mesophyll. Thus, the leaf-level photosynthetic response to diffuse light in sunflower occurred opposite to the expected canopylevel increases in LUE (Gu et al, 2002;Alton et al, 2007;Urban et al, 2007Urban et al, , 2012Alton, 2008;Kanniah et al, 2013;Williams et al, 2014;Cheng et al, 2015). We combined our leaf-level model with canopy-level observations of diffuse and direct light penetration to investigate this tradeoff (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A higher fraction of diffuse light tends to occur due to light-scattering particles in the atmosphere, such as clouds, aerosols, and anthropogenic emissions or volcanic ejecta (Mercado et al, 2009). At the canopy level, in both agricultural and natural systems, diffuse light illuminates more total leaf area, which has been repeatedly associated with increased light use efficiency (LUE [net primary productivity divided by absorbed photosynthetically active radiation]; Gu et al, 2002;Alton et al, 2007;Urban et al, 2007Urban et al, , 2012; Alton, 2008;Kanniah et al, 2013;Williams et al, 2014;Cheng et al, 2015) and an insignificant to positive effect on primary productivity (Kanniah et al, 2012). Although studies at the individual leaf level are less common, several lines of evidence suggest that leaf developmental environment underlies internal light absorption and subsequent photosynthetic responses to diffuse versus direct light.…”
mentioning
confidence: 99%
“…Data were collected as half-hourly averages (from 30 s readings). For further details on the eddy covariance system and micrometeorological measurements (Urban et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The locality is situated within a cool and humid area having high precipitation in the Moravian-Silesian Beskydy Mountains (Czech Republic, 49°30´N, 18°32´E, 800-900 m a.s.l. ; for detailed description of the site, Urban et al, 2012). The investigated forest was planted in 1981 with four-year-old Picea abies (L.) Karst.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation